KEPENTINGAN MESIR MENOLAK MERATIFIKASI KESEPAKATAN COOPERATION FRAMEWORK AGREEMENT (CFA) MENGENAI ATURAN PENGELOLAAN SUNGAI NIL - Aznor, Ariski; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describe about Egypt’s Interest to refused to ratify Cooperation Framework Agreement (CFA) about the rule of Management in Nile River. Nile River is Longest river in africa. And Shared by eleven countries. Nile River is primary water source of Egypt. Before CFA Exist, there was a nile river agreement signed by British Colonial and Egypt in 1929. This agreement ensured that Egypt would maintain its historic right of the Nile’s water,and allocated all water from the Nile to Egypt with no diversion allowed by upstream riparians. In 1959, Egypt and Sudan renegotiated their Nile sharing agreement Sudan recognized historical “rights over nile River for egypt and maintain their monopoly over the waters of the Nile, the 1959 treaty does not include any of the remaining upstream riparian countries and it forbids them from using the water or constructing any obstructions in Nile River. In 1999 First Organisation Nile riparian Countries, Nile Basin Initiative (NBI) Was Formed By 9 Nile Riparian Coutries. The main objective of the NBI was formed a cooperative framework agreement the Nile riparians countries and replace 1929 and 1959 agreement.Unfortunenately Egypt and Sudan Refused to ratify CFA Agreement.The theory that applied in this research is Realism and Level analysis in this research is State Level Analysis, researcher also use theory from about National Interest.The study found that the reason Egypt refused to ratify CFA Agreement are first,Egypt is dowstream nile riparians and has hot desert climate so Egypt depend on Nile River. Egypt Worry that CFA Agreement will allow upstream Nile riparian to diversion and build construction Nile and will impact to Nile River in Egypt. Second CFA don’t recognize Egypt’s historical right over Nile River and contradict Egypt’s constitution.Third Egypt’Economy depends on Nile river so Egypt Worry that CFA Agreement will allow upstream Nile riparian to diversion and build construction Nile and will impact to Egypt’Economy. Fourth, Nile River Issue is Security issue for Egypt. Almost all Egyptian citizen depend on Nile River, Egypt worry CFA agreement will impact to almost all egyptian citizen.Keywords : Nile River,Nile Basin Initiative,CFA,National Interest,Egypt